Neogene to Quaternary continental sedimentary dynamics in the Claromecó creek basin, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2021)
The Neogene to Quaternary continental sedimentary record of the southern Buenos Aires province has been the object of numerous stratigraphic and biostratigraphic studies. However, much has to be done concerning the evolution and sedimentary dynamics of this area. To this end, the Claromecó creek basin (CCB) was chosen as a case study. The aim of this work is to analyze the Neogene to Quaternary sedimentary record to understand the geological evolution of the basin. To reach this objective, a preliminary geomorphological study was carried out. Then, facies and associations of facies were defined in order to identify the sedimentary environment and to establish the ratio between accommodation space and sediment supply. This information was subsequently used to interpret the main controls on the sedimentation of the CCB.The CCB is located in the center of the southern Buenos Aires province. It covers an area of 3017.18 km2, from the northwestern flank of the Tandilia range to the Atlantic coastline (Fig. 1). The basin can be divided in three parts (upper, middle and lower) depending on slope, drainage and main geomorphologic characteristics (Fig. 2). Its infill is dominated by Neogene to Quaternary sediments lying over Palaeozoic shales and sandstones (Zárate and Rabassa, 2005; Ramos, 2005). The few sedimentological, stratigraphical and paleoenviromental studies are located close to the Atlantic coastline (Frenguelli, 1928; Isla et al., 1996; Isla et al., 2000; Prieto et al., 2014).A three step methodology was adopted. Firstly, a preliminary geomorphological study was carried out to understand the main geomorphological units and their relations with the landscape. The geomorphological setting was established with field observations and supported by SRTM. Secondly, eight sedimentological logs were made (Fig. 3). Facies and facies associations were defined according to Miall’s scheme (1985, 2014) (Table 1). Postdepositional processes were analysed and relative facies defined based on Mack et al. (1993) (Table 1). Finally, the interpretation of the depositional environments was performed considering the facies associations within the geomorphological units (Table 2). Accommodation space, sediment supply and controls were then defined and considered in a regional context.Two main geomorphological units were defined. The plain and elevations unit (U1) covers the upper and middle part of the basin. In the upper basin, the U1 is composed by an elevated plain in which the springs of the Claromecó creek are located. This plain evolves in a series of hills and elevations that cover discontinuously the middle part of the basin. U1 is characterized by reddish silty to conglomeratic calcretized fluvial sediments, which represent the substrate of the basin. In the middle and lower basin, this unit is eroded and forms large valleys, which represent the second geomorphological unit (U2). This unit is filled in by Late Pleistocene fluvial sediments that make up the present day floodplain.A total of eleven sedimentary facies and two postdepositional facies were defined (Table 1). These facies were grouped into six facies associations (FA) according to the geometry of the bodies and the interpreted depositional environments. These were subsequently grouped in accordance to the geomorphological units (Table 2). In this sense, U1 is composed by sheet flows (AF-A) forming mantles of matrix-supported conglomerates and sands (Gm and Sm facies) (Fig. 4a). Sheet-flow deposits are capped by amalgamated channel deposits of AF-B, composed of laminated and trough cross-stratified poorly sorted sands (Gm, Sh and St) (Fig. 4b). Both facies associations are capped by calcisols (AFP-C) (Fig. 4c, d). U2 is composed of sandy sheets (AF-C), floodplain deposits (AF-D), vegetated silty dunes (loess, AF-E) and marshy deposits (AF-F) (Fig. 5a). The sheet-like deposits are interpreted as unconfined channels filled by bars and locally preserved ripples (Ss, St and Sh). Floodplain deposits are broadly distributed in the basin and comprise massive to laminated silty sands with heterolithic lenses associated to secondary courses (Hl, Fl, Fm and Fr). Large and flat patchy dunes are present in the lower basin, composed of massive coarse silts (Fme and Fl) associated to eolian processes (loess). Close to the Atlantic coastline, whitish and laminated clayey silts are present, and are characterized by the presence of fresh and salty water gastropods (Hl, Fl y Fcf). U2 sedimentary successions are generally capped by hydromorphic paleosols (AFP-H) which are characterized by Fe-Mn rich nodules and rhizoliths (Fig. 6).The sedimentological succession can be divided in two subcycles (sensu Zarate, 2005) (Fig. 7). The first subcycle was developed between the late Miocene and middle-late Pliocene and is associated to the U1; the second subcycle was deposited between the late Pleistocene and the present and is linked to the U2 (Fig. 8). Both subcycles are followed by a stabilization stage (paleosols) that is related to a decrease of the accommodation space. For the Mio-Pliocene subcycle, this period can also be characterized as an erosional, no-depositional stage. This behavior is probably associated to a tectonic reactivation that occurred at some time after the middle-late Pliocene and that resulted in the formation of terrace and hills (U1) and the partial capture of the drainage of the CCB and nearby drainage basins (e.g., Quequén Grande and Quequén Salado rivers). In this context, the upper basin represents an elevated plain not affected by erosion and constituting a no-depositional surface. A regional discontinuous dynamic subsidence occurred during the Neogene and probably controlled the sedimentation and accommodation space in this area (Folguera et al., 2015).The late Pleistocene-Present subcycle responded to controls (changes in sea level and base level of continental systems) that did not significantly affect topography but rather resulted in facies variations. The development of eolian inland deposits (loess type), as well as marshy deposits restricted to the coastline, are probably related to the glacial/ interglacial stages that characterized the late Pleistocene-Holocene.
Keywords: Facies analysis, Fluvial systems, Geomorphology, Neogene, Southern Pampas.